Advances in repetitive transcranial magnetic stimulation for posttraumatic stress disorder: A systematic review. (June 2021) - Belsher, Bradley E.; Beech, Erin H.; Reddy, Madhavi K.; Smolenski, Derek J.; Rauch, Sheila A.M.; Kelber, Marija; Issa, Fuad; Lewis, Catrin; Bisson, Jonathan I.
Abstract: Repetitive transcranial magnetic stimulation (rTMS) as a treatment for posttraumatic stress disorder (PTSD) has gained interest over the past two decades. However, it has yet to be recommended in major treatment guidelines. We conducted a systematic review of randomized controlled trials to examine the efficacy of rTMS for PTSD. Thirteen studies with 549 participants were included in this review. We compared the effects of (1) rTMS versus sham, and (2) high-frequency (HF) versus low-frequency (LF) rTMS, on posttreatment PTSD scores and other secondary outcomes. We calculated the standardized mean differences (SMD) to determine the direction of effects, and unstandardized mean differences to estimate the magnitude of efficacy. At post-treatment, rTMS was superior to sham comparison in reducing PTSD (SMD = −1.13, 95% CI: −2.10 to −0.15) and depression severity (SMD = −0.83, 95% CI: −1.30 to −0.36). The quality of evidence, however, was rated very low due to small samples sizes, treatment heterogeneity, inconsistent results, and an imprecise pooled effect. HF rTMS was associated with slightly improved, albeit imprecise, outcomes compared to LF rTMS on PTSD (SMD = −0.19, 95% CI: −1.39 to 1.00) and depression (SMD = −1.09, 95% CI: −1.65 to −0.52) severity. Further research is required to advance the evidence on this treatment.